2009
DOI: 10.1002/hipo.20588
|View full text |Cite
|
Sign up to set email alerts
|

Move it or lose it—Is stimulation of the vestibular system necessary for normal spatial memory?

Abstract: Studies in both experimental animals and human patients have demonstrated that peripheral vestibular lesions, especially bilateral lesions, are associated with spatial memory impairment that is long-lasting and may even be permanent. Electrophysiological evidence from animals indicates that bilateral vestibular loss causes place cells and theta activity to become dysfunctional; the most recent human evidence suggests that the hippocampus may cause atrophy in patients with bilateral vestibular lesions. Taken to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 141 publications
(120 reference statements)
1
63
0
3
Order By: Relevance
“…Besides participating in formation of spatial memory [3,88,89], septohippocampal cholinergic neurons may also be important for sensorimotor processing in which activation of the vestibular system provides a sensory signal to assist in motor planning [90]. A number of studies have demonstrated that vestibular stimulation can improve cognition in humans (reviewed in [91][92][93]). Given that synaptic plasticity is altered in patients with Alzheimer's disease [94] and degeneration of basal forebrain cholinergic neurons is a pathological hallmark of this disease [14,15,95,96], vestibular stimulation may provide a novel treatment to improve hippocampus-dependent cognitive deficits in affected patients.…”
Section: Resultsmentioning
confidence: 99%
“…Besides participating in formation of spatial memory [3,88,89], septohippocampal cholinergic neurons may also be important for sensorimotor processing in which activation of the vestibular system provides a sensory signal to assist in motor planning [90]. A number of studies have demonstrated that vestibular stimulation can improve cognition in humans (reviewed in [91][92][93]). Given that synaptic plasticity is altered in patients with Alzheimer's disease [94] and degeneration of basal forebrain cholinergic neurons is a pathological hallmark of this disease [14,15,95,96], vestibular stimulation may provide a novel treatment to improve hippocampus-dependent cognitive deficits in affected patients.…”
Section: Resultsmentioning
confidence: 99%
“…Each one of these processes has been studied in rodents, primates, and humans from which several anatomical and behavioral correlates have been described. An example of these anatomical-clinical correlations is that a lesion involving the vestibular system results in decreased volume of the posterior hippocampus that causes impairment of navigational skills [8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Other vestibular regions include somatosensory cortex (area 2v, 3av), intraparietal sulcus (area VIP and MIP), posterior parietal cortex (area 7), area MST, frontal cortex (FEF), cingulum (cingulate vestibular cortex) and hippocampus. These regions are involved in various functions ranging from the perception of body rotation and translation, oculomotor and balance control, visual and postural vertical perception, to spatial navigation and memory (Angelaki et al, 2009;Berthoz, 1996;Smith et al, 2010).…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…In particular, how animals and human navigate in space -i.e. integrate and memorize the paths taken, elaborate and use cognitive maps of the spatial displacements -has been associated with vestibular processing (Berthoz et al, 1995;Mittelstaedt, 1999;Smith et al, 2010). In addition, vestibular signals, and the neural structures involved in vestibular processing, are crucial for distinguishing self-motion and object-motion (Straube and Brandt, 1987), perceiving the world as upright Mittelstaedt, 1999), elaborating an internal model of gravity and of one's body motion (Angelaki et al, 2004;Merfeld et al, 1999), as well as for visual perception related to gravity (Indovina et al, 2005;Lopez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%